39.3k views
4 votes
Graph the system below and write its solution.1y=x+3- 2x + y = 6Note that you can also answer "No solution" or "Infinitely many" solutions.10+6-Solution:-10

1 Answer

1 vote

EXPLANATION

The system of equations is given by the following expression:

(1) y = (1/2)x + 3

(2) -2x + y = 6

Substitute y= (1/2)x + 3


\begin{bmatrix}-2x+(1)/(2)x+3=6\end{bmatrix}

Simplifying:


-2x+(1)/(2)x+3=6

Adding similar elements:


-(3)/(2)x+3=6

Subtracting -3 to both sides:


-(3)/(2)x=6-3
\mathrm{Multiply\: both\: sides\: by\: }2
2\mleft(-(3)/(2)x\mright)=3\cdot\: 2

Simplify:


-3x=6

Divide both sides by -3:


(-3x)/(-3)=(6)/(-3)

Simplify:


x=-2
\mathrm{For\: }y=\mleft((1)/(2)\mright)x+3
\mathrm{Substitute\: }x=-2
y=(1)/(2)\mleft(-2\mright)+3

Remove parentheses: (-a) = -a


=-(1)/(2)\cdot\: 2+3
(1)/(2)\cdot\: 2

Cancel the common factor:


=1
=-1+3
\mathrm{Add/Subtract\: the\: numbers\colon}\: -1+3=2

=2

y=2


\mathrm{The\: solutions\: to\: the\: system\: of\: equations\: are\colon}
y=2,\: x=-2

Graph the system below and write its solution.1y=x+3- 2x + y = 6Note that you can-example-1
User Arnyminer Z
by
5.0k points